8.3: High Stability Against Light and Heat Based on the Top Gate Self‐Aligned a‐ IGZO TFTs under OLED Dislplay. (28th November 2018) - Wang, Guoying; Song, Zhen; Wang, Ling; Xu, Pan; Gai, Cuili; Lin, Yicheng; Yan, Liangchen; Wu, Zhongyuan
Abstract : Kinds of the top gate self‐aligned a‐IGZO TFTs were fabricated in order to apply in OLED display. The drift of the VTH under various stress conditions is studied systematically. It's found that when the temperature or the light is added, the drift of V TH is relatively large, such as PBTS and NBTIS, so it should be optimized in the process of the device preparation. Firstly, two kinds of devices are prepared. One is added the shield metal layer at the bottom of the device, and the other is without it. It's found that the VTH of the TFT is prone to large drift due to the lack of the protecting of the bottom shield metal. Secondly, the amount of oxygen in the device is particularly important for the stability of the device. Therefore, the stability of the device is investigated by changing the oxygen content of the buffer layer and the gate dielectric layer. Lastly, the drift of the VTH under various stress conditions for 7200s is less than 1V which is controlled within the circuit compensation range. The 14″ 8K UHD OLED display panel with good image quality was demonstrated finally.